Burnout and Patient Safety Culture among Emergency Department Nurses: A Cross-Sectional Analysis - Eka Lutfiatus Solehah; Komang Ayu Henny Achjar; Putu Ayu Lestarini; Nyoman Sri Ariantini; Yupin Aungsuroch (Journal Of Nursing Practice, 2026)
Background: Emergency departments (EDs) in major tourist destinations face intensified patient volume and cultural diversity, posing risks to nurse well-being and patient safety. Purpose: This study examined the effects of tourism-pressure workload and intercultural nursing competence on patient safety culture among emergency nurses in Bali, testing burnout as a mediating mechanism within the Job Demands Resources (JD–R) framework. Methods: A quantitative, cross-sectional survey was conducted from May to September 2025, coinciding with Bali’s peak tourist season. Using a total-sampling (census) approach, all eligible emergency nurses in participating public and private hospitals across Bali were invited, yielding 283 fully usable responses. Data were analyzed with partial least squares structural equation modeling (PLS-SEM): measurement quality was tested via Cronbach’s α, composite reliability, average variance extracted, and Fornell Larcker/HTMT discriminant-validity criteria, and structural paths and bootstrapped indirect (mediation) effects were tested with 5,000 resamples and bias-corrected 95% confidence intervals. Results: Tourism-pressure workload strongly increased burnout (β = 0.511, p < .001) and was negatively associated with patient safety culture (β = −0.249, p < .001). Contrary to the hypothesized protective direction, intercultural nursing competence was positively associated with burnout (β = 0.336, p < .001), while directly strengthening patient safety culture (β = 0.382, p < .001) as its strongest predictor. Burnout was negatively related to patient safety culture (β = −0.314, p < .001) and partially mediated the workload–safety relationship; the indirect path from intercultural competence through burnout was small and of the opposite sign to its direct effect (competing partial mediation). The model explained 55.2% of the variance in burnout and 65.6% in patient safety culture. Conclusion: Burnout is a central pathway through which tourism-driven demands erode safety culture, and intercultural competence carries a dual character protecting safety culture directly while imposing emotional demands when organizational support is insufficient. Integrated workload management, structured intercultural training, and burnout prevention are required.